Potensi Daun Kemangi (Ocimum basilicum Linn) sebagai Penangkal Radikal Bebas DPPH (2,2-Diphenyl-l-pycrylhidrazil radical) - Paini Sri Widyawati (agriTECH, 2005)
The commercial development of plants as sources of natural antioxidant to enhance health and food preservation is of current interest. It is related to phenolic compounds containing in foods and beverages to prevent many diseases. The natural antioxidant is more safety than the synthetic antioxidant such as TBHQ (tether butylated hydroxyquinone), BHT (butylated hydroxytoluene) and BHA (butylated hydroxyanisole). Basil (Ocimum basilicum Linn) contains a wide range of essential oils and is rich in phenolic compounds. These can be extracted by two methods i.e. soxhlet and hydrodistilation. The ethanolic extracts are resulted by soxhlet and essential oils are extracted by hydrodistilation. The oils are analyzed by gas chromatography to know the phenolic compound contents. The spectra are identified by standard compounds i.e. eugenol and linalool. These compounds are used because these are the dominant phenolic compounds in basil. The result showed that linalool spectrum is found in peak number 7 with 6,5 time retention. Total phenolics analysis showed that the highest concentration of them in the ethanolic extracts is 0,25 mg/g sample and in the essential oil is 5,20 mg/g essential oil. The DPPH (2,2-Dipheny1-1-pycrylhidrazil radical) free radical scavenging activity of the ethanolic extracts and the essential oil is tested and compared with I3-carotene and TBHQ. The result showed that the DPPH free radical scavenging activity of these antioxidant is in the order of [1-carotene > essential oil > ethanolic extracts > TBHQ respectively